1991
DOI: 10.1227/00006123-199111000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of 65 Tumors within the Spinal Cord: Surgical Results and the Importance of Preoperative Magnetic Resonance Imaging

Abstract: Between January 1984 and December 1990. 65 intramedullary spinal cord tumors were diagnosed and operated on. In this series, all patients underwent magnetic resonance imaging investigations and were operated on with the Cavitron ultrasonic surgical aspirator whenever necessary. Major surgical difficulties have been found in patients previously treated by radiotherapy with or without biopsy. We found magnetic resonance imaging to be a highly sensitive imaging procedure and the method of choice for visualizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
7

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 0 publications
2
50
0
7
Order By: Relevance
“…With these technological advances in mind, the clinical debate regarding appropriate treatment for spinal cord astrocytomas should be resumed. 14 In the present study, total and partial resections yielded better survival rates than biopsy alone in patients with spinal astrocytomas. Furthermore, a higher survival rate can be expected for cases with thoracic astrocytomas, compared to those with cervical astrocytomas.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…With these technological advances in mind, the clinical debate regarding appropriate treatment for spinal cord astrocytomas should be resumed. 14 In the present study, total and partial resections yielded better survival rates than biopsy alone in patients with spinal astrocytomas. Furthermore, a higher survival rate can be expected for cases with thoracic astrocytomas, compared to those with cervical astrocytomas.…”
Section: Discussionsupporting
confidence: 48%
“…Although we always attempted to perform total resection initially, it is not always possible to accomplish the procedure owing to the size, location, and nature of tumors. Because recent reports demonstrated that pilocytic astrocytomas can be totally resected, even if they look like high-grade malignancy tumors, 14 we should attempt at least partial, if possible total, resection of the tumor, especially for thoracic astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…Gross total resection (GTR) has been established as the gold standard in the treatment of intramedullary ependymoma, with series reporting 70-100% of ependymomas being radically resected [6,16,20,45,57] and long-term survival being the rule rather than exception. On the contrary, the therapeutical spectrum in infiltratively growing intramedullary astrocytomas ranges from histological verification and decompressive surgery with subsequent radiotherapy [64] to GTR, with 6-70% of intramedullary astrocytomas undergoing GTR [27,28,34,49,56,58,61,64].…”
Section: Introductionmentioning
confidence: 99%
“…7,42,62 Maximal resection is generally agreed to be the cornerstone of treatment for pediatric spinal ependymomas; 2,7,8,34,42,47,50 however, the addition of adjuvant radiation therapy after surgery is the subject of more debate. 2,7,8,48 While there are many studies on spinal ependymomas in adults, 11,12,[16][17][18]21,24,25,38,41,45,51,56,57,61,65 there are few papers on these tumors in children, and those that do exist tend to be small, single-institution retrospective studies that are not powered for statistical analysis stratified by tumor grade. 2,8,13,22,27,42,47,53 The goal of this paper is to use the nationally representative Surveillance Epidemiology and End Results (SEER) database to offer a population-based perspective on pediatric Grade II spinal ependymomas.…”
mentioning
confidence: 99%